Enhanced thermoelectric performance of band structure engineered GeSe1−xTex alloys. Issue 6 (23rd February 2021) - Sidharth, D.; Alagar Nedunchezhian, A. S.; Akilan, R.; Srivastava, Anup; Srinivasan, Bhuvanesh; Immanuel, P.; Rajkumar, R.; Yalini Devi, N.; Arivanandhan, M.; Liu, Chia-Jyi; Anbalagan, G.; Shankar, R.; et al.
Abstract : The power factor of GeSe enhanced and thermal conductivity decreased by Te substitution and thereby, GeSe0.80 Te0.20 exhibits high ZT . Abstract : Nanostructured thermoelectric materials of GeSe1− x Te x (0 ≤ x ≤ 0.2) alloys were prepared by mechanical ball milling, followed by consolidation under a hydrogen atmosphere and their structural, morphological, and thermoelectric properties were investigated. The XRD analysis confirms the structure of GeSe and the secondary phase of GeTe was observed in the sample with higher Te content. The electrical resistivity and Seebeck coefficient of GeSe1− x Te x decreased with increasing Te content due to the alloying effect. The carrier concentration increased up to four orders with increasing Te content in the alloy. The GeSe0.80 Te0.20 alloy shows a higher power factor of ∼222.17 μW m −1 K −2 at 708 K, due to high electrical conductivity compared to pure GeSe. Concomitantly, a low thermal conductivity was achieved for the alloys, especially at low temperatures due to large phonon scattering at the grain boundaries of nanostructured samples. The variation in the band structure of the compounds was examined using first-principles calculations, and the computational data confirm the convergence of bands. An improved thermoelectric figure of merit ( ZT ) of ∼0.22 at 708 K with a higher carrier concentration of 1.69 × 10 19 cm −3 was achieved for the p-type GeSe0.80 Te0.20 sample. The band gap of the GeSe1− x Te x alloy decreased with Te content as observed by computational studies, which resulted in high carrier concentration and ZT .